Effects of Brazil's Political Crisis on the Science Needed for Biodiversity Conservation - Magnusson, William E.; Grelle, Carlos E. V.; Marques, Márcia C. M.; Rocha, Carlos F. D.; Dias, Braulio; Fontana, Carla S.; Bergallo, Helena; Overbeck, Gerhard E.; Vale, Mariana M.; Tomas, Walfrido M.; Cerqueira, Rui; Collevatti, Rosane; et al. (Frontiers in Ecology and Evolution, 2018)
The effects of Brazil´s political crisis on biodiversity conservation are likely to be global. Brazil is not only the World´s most biodiverse nation, it is responsible for the greater part of the Amazon forest, which regulates the climate and provides rain to much of southern South America. Brazil was a World leader in satellite monitoring of land-use change, in-situ biodiversity monitoring, reduction in tropical-forest deforestation, protection of indigenous lands, and a model for other developing nations. Coordinated public responses will be necessary to prevent special-interest groups from using the political crisis to weaken environmental legislation and law enforcement.